Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja Karyawan pada Toko Sinar Welisa Jaya Citraland Surabaya - Ahen Nikolas Banoet; Bambang Karnain; Harsono Teguh Santoso; Achmad Daengs G.S; Rina Dewi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine the influence of organizational culture and leadership style on employee performance at Sinar Welisa Jaya Store. The research method used is a quantitative method. The data processed are the results of a questionnaire with a population of 60 and a sample of 37.5 respondents. The data analysis technique used is the classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis, as well as hypothesis testing namely the coefficient of determination, f test, t test. The results of the study, based on the test results, indicate that organizational culture and leadership style have a significant influence on employee performance at the Sinar Welisa Jaya Citraland Surabaya store. This is evidenced by the coefficient of determination, which shows a correlation between employee performance and all independent variables (organizational culture and leadership style) of 0.589, or 59.8%. This means that 59.8% of the variation or change in employee performance is jointly influenced by organizational culture and leadership style, while the remaining 40.2% of the variation or change in employee performance is caused by other variables not included in this study.